A Rare Case of Burkitt Lymphoma in a 13-year-girl - Büşra Yılmaz; Efsun Somay; Bermal Hasbay (Journal of Pediatric Research, 2021)

(untitled)
Burkitt lymphoma is rare Non-Hodgkin’s lymphoma type in childhood. The differential diagnosis includes dental infection and osteomyelitis. Therefore, patients often refer to the dentist first. Early diagnosis has great importance on prognosis. We aimed to broaden the perspective of dentists about this disease and confirm the diagnosis radiographically and clinically.